Ensembled evaluations of habitat suitability for prioritizing lesser prairie‐chicken conservation - Morgan J. Solomon; Kent A. Fricke; Carter Kruse; Lance B. McNew (Ecosphere)
Abstract Populations of lesser prairie‐chickens (Tympanuchus pallidicinctus, hereafter “prairie‐chickens”) in the Mixed‐Grass Prairie Ecoregion of the southern Great Plains have been projected to go extinct in the next 100 years unless targeted conservation efforts are implemented to increase the size and connectivity of subpopulations through either translocation or habitat restoration. To expand on current conservation efforts, we used ensemble approaches to identify potential habitat and assist managers in accurately prescribing management actions for prairie‐chicken conservation. We developed lek‐based relative habitat suitability models within the Mixed‐Grass Prairie Ecoregion using both resource selection function and Random Forest classification trees and calculated ensembled predictions of relative habitat suitability across all models. Next, we conducted a least‐cost path analysis to identify potential corridors connecting potentially suitable, unoccupied habitat to current subpopulations. Ensembled predictions identified 4575 km2 of potential prairie‐chicken habitat both occupied and unoccupied. We identified three contiguous areas of potentially suitable and unoccupied habitat (28–74 km2) that could potentially harbor a self‐sustaining population. Ensembled predictions can be used to strategically implement restoration projects to enhance the quality and connectivity of habitat within and adjacent to the species' current distribution. Least‐cost path analyses revealed a low degree of connectivity between areas of occupied and unoccupied habitat, highlighting the importance of implementing habitat improvement projects to increase connectivity for prairie‐chicken persistence. Our results provide information that professionals may use to prioritize conservation delivery for prairie‐chickens in the Mixed‐Grass Prairie Ecoregion.